67P/Churyumov–Gerasimenko active areas before perihelion identified by GIADA and VIRTIS data fusion. Issue 2 (3rd December 2018) - Longobardo, A; Della Corte, V; Ivanovski, S; Rinaldi, G; Zakharov, V; Rotundi, A; Capaccioni, F; Fulle, M; Filacchione, G; Palomba, E; Palumbo, P; Capria, M T; et al.
Abstract: We characterized 67P/Churyumov–Gerasimenko's cometary activity during its inbound arc before perihelion (2014 August–2015 January). We focused on the geomorphological regions of the Northern hemisphere observed by the ESA/Rosetta space probe during this time period. The GIADA dust detector characterized the physical properties of the fluffy and compact particles ejected from the nucleus; the VIRTIS imaging spectrometer detected exposed water ice. We identified specific cometary active areas by adopting the following GIADA and VIRTIS indicators: (a) The decrease with increasing temperature of the centre of the 3.2 μ m absorption band and of the spectral slope between 1.1 and 1.9 μ m, as measured by VIRTIS, which are both possible effects of water ice exposition. (b) The number of fluffy and compact particles ejected from a specific region, which we determined by tracing dust particles in the coma, as detected by GIADA, back down to the nucleus. The correlation between GIADA and VIRTIS indicators led us to conclude that dust emission causes exposition of water ice on the surface of the nucleus, and fluffy and compact particles have common ejection regions; their lack of correlation in the coma is due to spread induced by their different velocities. We find that the most active regions are located in the neck (Hapi and Seth) and in the body (Ash, Babi, and Aten) of the comet. These regions are also the ones most illuminated during the considered observation period, indicating that insolation is the main, if not only, driver of cometary activity.